Differences in Student Aggressive Behavior Judging from Peer Conformity and Its Implications in Counseling Guidance Services - Raju Haser; Yeni Karneli (Universitas Negeri Padang, 2020)
This research is motivated by the phenomenon of high school students where students like to interact and mingle with their peers and form a play group that unconsciously shapes attitudes and behavior in accordance with the values and norms in the group, and tends to show aggressive behavior. This study aims to describe how the differences in aggressive behavior of students in school in terms of peer conformity based on several aspects, namely: (1) compactness (2) agreement (3) obedience. This type of research is quantitative with a comparative descriptive approach. The sample of this research was 271 students of SMAN 1 Gunung Talang students who were selected based on the Propotional Random Sampling technique. The research instrument was a questionnaire of aggressive behavior and peer conformity. Data were processed using descriptive statistical analysis techniques and t-test analysis. The results revealed that: (1) the aggressive behavior of students of SMAN 1 Gunung Talang was generally in the moderate category with a percentage of 39.48%, (2) peer conformity of SMAN 1 Gunung Talang students was generally in the moderate category with a percentage of 38.75 %, (3) there is a significant difference between the aggressive behavior of students in terms of peer conformity, where the average aggressive behavior is smaller than the average peer performance.